EKSPLORASI ETNOMATEMATIKA MOTIF RUMAH ADAT KAJANG LAKO JAMBI DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SD - Sartika, Hana Yuli; Sastrawati, Eka; Budiono, Hendra (Universitas Bhinneka PGRI, 2024)
This research aims to (1) Describe the ethnomathematics contained in the Kajang Lako Jambi Traditional House Motif (2) Describe what mathematical concepts are contained in the Kajang Lako Jambi Traditional House Motif which can be used in elementary school mathematics learning. In this research, researchers used qualitative research with an ethnographic approach. The instrument used by researchers is a human instrument, researchers are directly involved in the field including observation, interviews, literature study and documentation. The data analysis techniques used are data reduction, triangulation, data presentation, and drawing conclusions. The results of this research are mathematical concepts found in the Kajang Lako Jambi traditional house, such as geometry, measurement and arithmetic. It can be concluded that the ethnomathematics exploration of the Kajang Lako Jambi traditional house motif can be used as a source of mathematics learning for high grade elementary school students in improving their understanding of mathematical concepts.